Malignancy of eye melanomas originating in the retinal pigment epithelium of transgenic mice after genetic ablation of choroidal melanocytes. - Mintz, B (1992)
Eye tumors of the retinal pigment epithelium (RPE) have been thought generally to be benign, whereas choroidal ones are malignant. To test this assumption in mice, the W/Wv (Kit) mutant genotype was introduced into melanoma-prone transgenic mice whose recombinant simian virus 40 transforming sequences are specifically expressed in pigment cells. W/Wv causes programmed death of neural crest-derived pigment cells, including choroidal ones, but leaves intact the brain-derived pigment cells, such as those in the RPE. Dysplastic cells arose in the RPE, contiguous with frank melanotic neoplasms. Invasion of the optic nerve, and tumor growth outside the orbit, attested to the malignancy of these RPE-derived melanomas. The widespread melanosis previously seen in mice with this transgene was absent when W/Wv was added, thus validating its chief origin from neural crest cells.